Diversion Regulation for Public Transport Drivers in Criminal Justice to Enhance Road Safety (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Road transportation plays a vital role in Indonesia’s economic mobility, where public transport drivers are responsible for safely moving people and goods. National data from Social Security Administration and the Indonesian National Police (Korlantas) shows that 61% of traffic accidents are caused by human error, including drivers’ lack of skill, negligence, and reckless behavior, followed by 9% vehicle factors and 30% infrastructure and environmental factors.Purposes of the Research: This article examines the legal framework of diversion as an alternative settlement mechanism for traffic crime cases committed by public transport drivers within Indonesia’s criminal justice system. It also analyzes the requirements of diversion under Articles 310 and 311 of Law Nomor 22 of 2009 and evaluates its implementation in Purwakarta Regency based on fairness, legal certainty, and restorative justice principles.Methods of the Research: This study employs an empirical legal research method to observe how the law operates in practice within society. Data were gathered through field observation, documentation, and analysis of traffic accident cases involving public transport drivers in Purwakarta. The empirical approach enables the researcher to examine the effectiveness of diversion policies within real criminal justice processes.Findings of the Research: The findings show that the regulation of diversion for public transport drivers in traffic accident cases has been effective in Purwakarta. In fatal accident cases, suspects are charged under Article 310(4) of Law Number 22/2009 jo. Article 77 of the Criminal Code. However, when the driver also suffers serious injuries requiring prolonged treatment, diversion may proceed, enabling restorative and legally certain case resolution within the criminal justice system.